Propelling participation - Ayub Ali, Md.; Hossain, Md. Shahdat; Halder, Joseph; NGO Forum for Drinking Water Supply and Sanitation (Bangladesh) (Dhaka : NGO Forum for Drinking Water Supply & Sanitation, 2000)
With reference to Community Managed WatSan Programme of NGO Forum for drinking water supply and sanitation in Bangladesh.
Includes bibliographical references (p. 89).
Keywords: Water-supply -- Bangladesh; Sanitation -- Bangladesh; Community Managed WatSan Programme (Bangladesh)